When I'm 64.
By 2030 there will be about 70 million people in the United States who are older than 64. Approximately 26 percent of these will be racial and ethnic minorities. Overall, the older population will be more diverse and better educated than their earlier cohorts. The range of late-life outcomes is very dramatic with old age being a significantly different experience for financially secure and well-educated people than for poor and uneducated people. The early mission of behavioral science research focused on identifying problems of older adults, such as isolation, caregiving, and dementia. Today, the field of gerontology is more interdisciplinary. When I'm 64 examines how individual and social behavior play a role in understanding diverse outcomes in old age. It also explores the implications of an aging workforce on the economy. The book recommends that the National Institute on Aging focus its research support in social, personality, and life-span psychology in four areas: motivation and behavioral change; socioemotional influences on decision-making; the influence of social engagement on cognition; and the effects of stereotypes on self and others. When I'm 64 is a useful resource for policymakers, researchers and medical professionals.